Influence of varying crude protein levels and balanced amino acids on the performance and haematological characteristics of laying hens at the second phase of production (2013)
Varying levels of dietary crude proteins and balanced amino acids were fed to layers for a period of eight weeks starting from the twenty-sixth week of age of birds and six weeks into egg production. Effects on performance and haematological characteristics were investigated at this second phase of production. Sixty Black Nera hens were randomly allotted into four (4) dietary treatments, containing the following levels of crude protein 14%, 15%, 16%, 17% and the metabolizable energy was iso-caloric for each treatment. The results showed that there were no significant differences (P > 0.05) observed for lymphocyte, Haemoglobin (Hb), Packed Cell Volume (PCV), Red Blood Cell (RBC) and White Blood Cell (WBC), these haematological parameters were within the range for healthy birds. Thus crude protein level of 14% can be used in diets of layers at the second phase of production provided that adequate amino acids are given, without adverse effect on egg laying, feed intake and measured blood parameters.